A copper-clad lithiophilic current collector for dendrite-free lithium metal anodes. Issue 4 (6th January 2020) - Chen, Ke; Pathak, Rajesh; Gurung, Ashim; Reza, Khan M.; Ghimire, Nabin; Pokharel, Jyotshna; Baniya, Abiral; He, Wei; Wu, James J.; Qiao, Qiquan (Quinn); Zhou, Yue
Abstract : A flexible copper-clad lithiophilic current collector was designed for high coulombic efficiency dendrite-free Li metal anodes. Abstract : Lithium (Li) metal has been considered as one of the most attractive anode materials of Li batteries due to its high theoretical capacity and low electrochemical potential. However, dendrite formation and large volume change during battery operation hinder its commercialization. Here, we created a three-dimensional (3D) light-weight and mechanically flexible copper-clad carbon framework (CuCF) as a lithiophilic current collector. The CuCF can be made by scalable pyrolysis of a melamine–formaldehyde foam (MF) followed by copper electroplating. The carbon framework (CF) without copper cladding has a lower conductivity (4.32 × 10 −4 S cm −1 ) and fewer non-uniform lithium nucleation sites, leading to lithium dendrite growth during plating/stripping. By surface engineering with copper-cladding, the CuCF has a much higher conductivity (1.38 × 10 −2 S cm −1 ) and more Li nucleation sites which allow a uniform and smooth Li deposition. Moreover, the excellent mechanical flexibility and enlarged surface area of the CuCF current collector can accommodate volume expansion and reduce local current density. As a result, a dendrite-free Li metal anode is achieved with a high coulombic efficiency of 99.5% even after 300 plating/stripping cycles (∼1200 hours). Significantly, it can last for more than 170 cycles at a high current of 5 mA cm −2 in a symmetric cell cycling test. Furthermore, a Li/lithium iron phosphate (LFP) cell exhibits a long cycling life at a high current of 1C.